2017
DOI: 10.15171/joddd.2017.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated torque tightening on total lengths of implant abutments in different internal implant‒abutment connections

Abstract: Background. Since the misfit of crown has an important role in clinical performance of implant-supported prostheses, and due to the impact of the settling effect on misfit, the aim of this study was to investigate the impact of torque forces on the total lengths of narrow and short implant abutments in different internal implant‒abutment connections. Methods. In four different implant‒abutment connections, 8 analog implants with a normal diameter (4 mm) and narrow abutment (4.5 mm) were selected from groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The abutment screw becomes slightly loosened when the abutment is completely combined with the implant by opening the implant wall. Because of the preload loss from such an abutment sinking and settling effect, repeated screw tightening is essential [18,22].…”
Section: Internal Friction Connection: Frictional Interfacementioning
confidence: 99%
“…The abutment screw becomes slightly loosened when the abutment is completely combined with the implant by opening the implant wall. Because of the preload loss from such an abutment sinking and settling effect, repeated screw tightening is essential [18,22].…”
Section: Internal Friction Connection: Frictional Interfacementioning
confidence: 99%
“…On the other hand, the use of different torques on analogs and implants did not influence the height of the prosthetic abutment, showing that the use of the analog during the prosthesis fabrication is not directly related to future mismatches associated with the crown height but rather the applied torque. A study by Saber et al [ 7 ] showed the discrepancy of the abutment height between the different types of implant platforms, showing greater discrepancy in the external hexagon system. However, in the present study, we did not consider the simulation of the laboratory phase of prosthesis confection, using analog, as done in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Microsoft Office 2013 Excel was used for data tabulation and Prisma GraphPad 6.0 software was used for statistical calculations and graphic production. The sample size was based on previous studies [ 7 , 8 ], considering the power of 80%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the implant top is gradually opened, causing the abutment to sink down, which loosens the abutment screw, leading to a need for periodic retightening. 175,241,242 Otherwise, abutment movement increases, leading to destruction of the soft tissue seal, and subsequent bacterial attack. Clinically, re-tightening can be performed several times if necessary.…”
Section: Control Of the Implant-abutment Interfacementioning
confidence: 99%